An Interview-Based Approach to Assess Angler Practices and Sea Turtle Captures on Mississippi Fishing Piers - Cook, Melissa; Dunch, Victoria S.; Coleman, Andrew T. (Frontiers in Marine Science, 2020)
During 2010 – 2015, the Mississippi Sea Turtle Stranding and Salvage Network (STSSN) documented 1,073 sea turtles, primarily juvenile Kemp’s ridleys (Lepidochelys kempii), incidentally caught by recreational anglers. Due to increases in interactions, an angler interview survey was conducted during 2013 at six Mississippi fishing piers. Anglers were interviewed about fishing practices and sea turtle interactions. Interviewers conducted outreach and distributed Rehabilitation Hotline business cards. Angler participation was 86%, and over 60% used J-hooks and were not targeting specific species, which was similar to data collected from incidental captures reported to the STSSN. Over 58% of anglers used dead shrimp followed by cut up fish for bait. This greatly differs from STSSN reported captured sea turtles where 60% were caught on cut up fish and only 6% on dead shrimp. Over 18% of participants captured at least one sea turtle in the last 12 months. Anglers stated that nearly half of the sea turtles were taken for rehabilitation, 41% were released by the angler and 10% broke the line and swam away. Only 60% of anglers reported the capture because many were unaware they should report it. During and after the survey period, there was an increase in reported incidental captures, possibly indicating outreach is an effective means of increasing awareness and reporting. Recently, NOAA Fisheries developed a survey that can be used nationally to conduct similar research. We recommend conducting angler surveys every few years unless there is a noticeable change in incidental capture trends or angler practices.